Mogul European Communications between the years ( 643/650) AH _(1245/1253)AD The aim and the reasons of failure - Mhanna, Osama (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This paper presents the papal attempt to ally with the Mongols who aimed to achieve two basic objectives: surround the Islamic world and spread the Christianity among the Mongols in order to attract them on one hand and prevent their malice on the other. At the time the Mongols are attacking Baghdad, the Crusaders can attack Egypt. In order to achieve that, the papal authority sent many reconciliations that began with John Alcaerbini reconciliation followed by Andrei Lunga mission then Anselmo Ocelin mission. The content of the messages of those reconciliations was the call to follow the Christianity and to prevail peace between the Europeans and the Mongols, but the reaction of the Mongols was disappointing because they asked the Pope and the King's of Europe to attend by themselves and show their loyalty and obedience to them. However, these reconciliations were not only restricted to the religious authority (the papacy), but also moved to the political side, by the King Louis IX showing a great desire in allying with the Mongols and sending several reconciliations to achieve it. But in vain, because it only assured to the papal authority and the King Louis that the idea of alliance with the Mongols at that period was impossible in the policy that the Mongols followed with all the world's population: either by obedience or by war.